Physiologic dentin regeneration: its past, present, and future perspectives - Lee, Myungjin; Lee, Yoon Seon; Shon, Won-Jun; Park, Joo-Cheol (Frontiers in Physiology, 2023)
Regenerative dentistry has rapidly progressed since the advancement of stem cell biology and material science. However, more emphasis has been placed on the success of tissue formation than on how well the newly generated tissue retains the original structure and function. Once dentin is lost, tertiary dentinogenesis can be induced by new odontoblastic differentiation or re-activation of existing odontoblasts. The characteristic morphology of odontoblasts generates the tubular nature of dentin, which is a reservoir of fluid, ions, and a number of growth factors, and protects the inner pulp tissue. Therefore, understanding the dynamic but delicate process of new dentin formation by odontoblasts, or odontoblast-like cells, following dentinal defects is crucial. In this regard, various efforts have been conducted to identify novel molecules and materials that can promote the regeneration of dentin with strength and longevity. In this review, we focus on recent progress in dentin regeneration research with biological molecules identified, and discuss its potential in future clinical applications.